Chitosan inhibits platelet-mediated clot retraction, increases platelet-derived growth factor release, and increases residence time and bioactivity of platelet-rich plasma in vivo. (10th November 2017) - Deprés-Tremblay, Gabrielle; Chevrier, Anik; Tran-Khanh, Nicolas; Nelea, Monica; Buschmann, Michael D
Abstract: Platelet-rich plasma (PRP) has been used to treat different orthopedic conditions, however, the clinical benefits of using PRP remain uncertain. Chitosan (CS)–PRP implants have been shown to improve meniscus, rotator cuff and cartilage repair in pre-clinical models. The purpose of this current study was to investigate in vitro and in vivo mechanisms of action of CS–PRP implants. Freeze-dried formulations containing 1% (w/v) CS (80% degree of deacetylation and number average molar mass 38 kDa), 1% (w/v) trehalose as a lyoprotectant and 42.2 mM calcium chloride as a clot activator were solubilized in PRP. Gravimetric measurements and molecular/cellular imaging studies revealed that clot retraction is inhibited in CS–PRP hybrid clots through physical coating of platelets, blood cells and fibrin strands by chitosan, which interferes with platelet aggregation and platelet-mediated clot retraction. Flow cytometry and ELISA assays revealed that platelets are activated and granules secreted in CS–PRP hybrid clots and that cumulative release of platelet-derived growth factor (PDGF-AB) and epidermal growth factor is higher from CS–PRP hybrid clots compared to PRP clots in vitro . Finally, CS–PRP implants resided for up to 6 weeks in a subcutaneous implantation model and induced cell recruitment and granulation tissue synthesis, confirming greater residency and bioactivity compared to PRP in vivo .